The subclass heterogeneity of pig IgG - Franek, F (Veterinary immunology and immunopathology, 1987)
The recognition and distinction of pig IgG subclasses is a difficult task because no pathological monoclonal immunoglobulins of pig origin are available. Attempts at elucidating the subclass composition of pig IgG based on subfractionation of pooled IgG and preparation of antisera has led to only partial success. Chemical evidence for heterogeneity of the constant portion of pig gamma-chains pointed to the existence of more than one subclass; a final answer to the question of the number of subclasses could not be obtained. Functionally different antibodies of the IgG class may be isolated from immune sera collected at various stages of the immune response. Precipitating and nonprecipitating anti-dinitro-phenyl (DNP) antibodies differ chiefly in their capacity for forming insoluble complexes with DNP-carrier proteins. Examination of these antibodies by physical methods showed that the precipitating antibody is less compact, more flexible and that the distance between the two binding sites on the same molecule are greater than for the nonprecipitating anti-DNP antibody. The precipitating antibody is very resistant to cleavage by pepsin compared to the non-precipitating antibody. This resistance, together with the differences in the molecular parameters described above provides evidence that precipitating and nonprecipitating anti-DNP antibodies in swine are representatives of separate IgG subclasses. Mouse monoclonal antibodies to pig IgG show a degree of selectivity for certain IgG subpopulations when tested against pooled pig IgG. The limited number of monoclonal antibodies currently available does not allow final conclusions to be drawn on the number of pig IgG subclasses.
Keywords: Models, Molecular; Antibody Formation; dinitrofenoly; imunoglobulin G; Precipitin Tests; Molecular Sequence Data; molekulární sekvence - údaje; Antibodies, Monoclonal; zvířata; molekulární modely; Swine; Amino Acid Sequence; Dinitrophenols; tvorba protilátek; precipitinové testy; monoklonální protilátky; Animals; Immunoglobulin G; prasata; sekvence aminokyselin